2011
DOI: 10.20355/c58c77
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Kids in School: A Study Examining the Long-Term Impact of Afterschool Enrichment Programs on Students’ High School Dropout Rates

Abstract: Despite the potential benefits of afterschool programs, much of the related research has been limited to an examination of only their immediate or short-term effects. The LA's BEST afterschool program has been in operation for more than 20 years, providing researchers with a unique opportunity to explore the long-term effects of afterschool programming. This study examined the dropout rates of the LA's BEST afterschool participants and compared them to a stratified random district sample that was matched to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…One study 65 reported a relative improvement of 7.3% on the Iowa Test of Basic Skills (www.riversidepublishing.com/products/itbs/), a standardized test that assesses reading, language arts, math, social studies, and science knowledge combined. Favorable effects of OSTA programs were shown for high school completion across 4 studies, 57,61,62,66 as evidenced by a median 6.8% relative change in intervention populations compared with control populations (range, −1.1% to 15.0%). Similar improvements were found for college enrollment in 3 studies, 57,61,62 with a median relative change of 7.0% (range, 2.7%–24.0%).…”
Section: Evidence Synthesismentioning
confidence: 98%
See 2 more Smart Citations
“…One study 65 reported a relative improvement of 7.3% on the Iowa Test of Basic Skills (www.riversidepublishing.com/products/itbs/), a standardized test that assesses reading, language arts, math, social studies, and science knowledge combined. Favorable effects of OSTA programs were shown for high school completion across 4 studies, 57,61,62,66 as evidenced by a median 6.8% relative change in intervention populations compared with control populations (range, −1.1% to 15.0%). Similar improvements were found for college enrollment in 3 studies, 57,61,62 with a median relative change of 7.0% (range, 2.7%–24.0%).…”
Section: Evidence Synthesismentioning
confidence: 98%
“…Specifically, among studies that reported race/ethnicity, 60% were majority black ‡ and S. Ross, et al (unpublished data, 1996) and among those reporting SES, 84% were majority low SES. § The largest proportion of programs were reading-focused | and general academics ¶ (40% each), followed by math-focused 29,42,49,52,54,61,77 (12%) and minimal academics 45,66,72,81 (7%); one program 77 had separate math- and reading-focused arms. Of 51 programs for which didactic approach was reported, most (47%) involved group instruction, ** 33% involved tutoring or individualized instruction, †† and the remainder (20%) used mixed approaches.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…STAR -Chetty, Friedman, Hilger, Saez, Diane, and Yagan (2011); Krueger (2003). LA's BEST - Goldschmidt and Huang (2007); Huang, Gribbons, Kim, Lee, and Baker 2000; Huang, Kim, Marshall, and Pérez (2005). CSP -McCord (1978).…”
Section: Schoolingmentioning
confidence: 99%
“…Other programs, such as Communities in Schools, 40 provide diverse services to students at risk of academic failure, and also include guidance, counseling, and enrichment activities. Los Angeles’ Better Educated Students for Tomorrow (BEST) 41 is an afterschool program for Los Angeles students enrolled in kindergarten through fifth grade. Students are provided with homework assistance, social–emotional development programs, recreational opportunities, and access to performing arts.…”
Section: Evidence Synthesismentioning
confidence: 99%